Model of Assistance for BUMDesa Fisheries Business Groups in Improving Community Economy - Mohammad Ato’Illah; Kasno Kasno (Mahameru Publisher, 2022)
The field of community empowerment is one of the Government's efforts to support the community's economy. One of the efforts to mobilize the economic potential in villages that spread across Indonesia, the government supports and encourages the formation of Village Owned Enterprises (BUMDesa). This is like what already exists in the village of Labruk Lor, Lumajang District, Lumajang Regency. However, there are obstacles related to the development of processed products in the fisheries unit at the Bumdesa Labruk Lor. The purpose of this research is to provide knowledge about product processing development activities and provide hands-on training. The method used is in the form of active participation in mentoring activities, lectures and practices. This activity was carried out for 6 months by involving the local government sector and universities. The results show that the Bumdes management understands the benefits that will be obtained from developing processed products from the fisheries unit, besides that it is hoped that this activity will also have an impact on increasing income for Bumdes.